The study of Russian agribusiness development factors applying statistical models - Vladimir Аnatolievich Shibaykin (Ekonomika Poljoprivrede (1979), 2010)
The dynamics of Russian agribusiness on the basis of the dynamics of agricultural production is overviewed in the article. Using these statistical models the author studies the factors affecting the development of Russian agribusiness.